A comparative analysis of proximity measures to determine the Lithuanian population structure - Molytė, Alma; Urnikytė, Alina (Lietuvos matematikos rinkinys, 2021)
In this paper the multidimensional scaling, the principal coordinate and principal component methods for the Lithuanian population structure have investigated, taken that the proximity measures are Euclid, Gower, Bray-Curtis, Kulczynski, Jaccard and Morisita. The genome-wide single nucleotide polymorphism genetic data analyzed. A comparative analysis of proximity measures performed. The results of visualization are also presented.